Experimental Criminology and the Free-Rider Dilemma - Koehler, Johann A. (The British journal of criminology, 2021)
Experimental criminology promises a public good: when experiments generate findings about criminal justice interventions, everyone benefits from that knowledge. However, experimental criminology also produces a free-rider problem: when experiments test interventions on the units where problems concentrate, only the sample assumes the risk of backfire. This mismatch between who pays for criminological knowledge and who rides on it persists even after traditional critiques of experimental social science are addressed. We draw from medicine and economics to define experimental criminology’s free-rider problem and expose a dilemma. Either we distribute the costs of producing policy-actionable knowledge to the entire beneficiary population or we justify isolating the risk of experimental harm on that class of the population where ethical concerns are most acute.